1998
DOI: 10.1177/104973159800800603
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Georgia Legislative Waiver's Effectiveness in Deterring Juvenile Crime

Abstract: In an effort to curb the reported increases in violent juvenile crime, the growing trend of state legislatures is the removal of crimes specified as serious from the jurisdiction of the juvenile court. Having been legislatively waived, these offenses are placed within the jurisdiction of the superior court, and the offender, regardless of age, is tried as an adult. This investigation reports on the deterrent effect of the Georgia legislative waiver passed in 1994. A quasi-experimental cohort design is used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…These results support several conclusions. First, these results add to growing evidence that statutory boundaries between the juvenile and adult justice systems as well as changes to these boundaries have few observable effects on offender behavior (Hjalmarsson, 2009;Jensen and Metsger, 1994;Lee and McCrary, 2009;Risler et al, 1998;Singer and McDowall, 1988). This may be because of the absence of meaningful treatment differences or, consistent with other research on juvenile decision making, the insensitivity of juveniles to these incentives.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These results support several conclusions. First, these results add to growing evidence that statutory boundaries between the juvenile and adult justice systems as well as changes to these boundaries have few observable effects on offender behavior (Hjalmarsson, 2009;Jensen and Metsger, 1994;Lee and McCrary, 2009;Risler et al, 1998;Singer and McDowall, 1988). This may be because of the absence of meaningful treatment differences or, consistent with other research on juvenile decision making, the insensitivity of juveniles to these incentives.…”
Section: Discussionsupporting
confidence: 79%
“…Although the aggregate‐level effects of a shift in the entire age boundary between the juvenile and adult justice systems have not been explored recently, the findings from evaluations of prior and more limited changes to the exclusive jurisdiction of the juvenile justice system have provided limited evidence for such cohort‐wide behavioral effects (Jensen and Metsger, ; Risler, Sweatman, and Nackerud, ; Singer and McDowall, ). Weak evidence has generally been found for the importance of boundary changes.…”
Section: Juvenile Offending and Agementioning
confidence: 99%
“…The authors compare the rate of total juvenile arrests in Idaho in the 4 years before and after the statute was enacted with the rate of total juvenile arrests during that period in Wyoming and Montana. Risler, Sweatman, and Nackerud (1998) examine the effect of a 1994 Georgia law requiring the transfer of juveniles over 13 years of age who were charged with the most serious criminal offenses (namely, murder, manslaughter, rape, child molestation, and armed robbery). The authors compare the total juvenile arrest rates in Georgia in the 2 years before and after the law went into effect.…”
Section: Prior Literaturementioning
confidence: 99%
“…In examining the criminal sentencing of adult offenders, they found that those adult defendants who pled guilty and did not go to criminal trial were significantly less likely to receive a severe sentence than their adult counterparts who did not plead guilty and who did go to trial. As expressed by other researchers (Myers, ; Redding, ; Risler, Sweatman, & Nackerud, ), one potential reason for this difference in findings is that, during criminal trials, felony juvenile offenders may be perceived as less of a public safety threat than their adult offender counterparts; therefore, these juveniles receive more lenient sentences. Although there is no published research on this issue that can help to substantiate this possibility, the current study did find that youth who received a trial were significantly more likely to be sentenced to probation or restitution than juveniles who pled guilty and did not go to trial.…”
Section: Discussionmentioning
confidence: 91%